Relationship Between Visuospatial Neglect and Kinesthetic Deficits After Stroke. (May 2015) - Semrau, Jennifer A.; Wang, Jeffery C.; Herter, Troy M.; Scott, Stephen H.; Dukelow, Sean P.
Background. After stroke, visuospatial and kinesthetic (sense of limb motion) deficits are common, occurring in approximately 30% and 60% of individuals, respectively. Although both types of deficits affect aspects of spatial processing necessary for daily function, few studies have investigated the relationship between these 2 deficits after stroke. Objective. We aimed to characterize the relationship between visuospatial and kinesthetic deficits after stroke using the Behavioral Inattention Test (BIT) and a robotic measure of kinesthetic function. Methods. Visuospatial attention (using the BIT) and kinesthesia (using robotics) were measured in 158 individuals an average of 18 days after stroke. In the kinesthetic matching task, the robot moved the participant's stroke-affected arm at a preset direction, speed, and magnitude. Participants mirror-matched the robotic movement with the less/unaffected arm as soon as they felt movement in their stroke affected arm. Results. We found that participants with visuospatial inattention (neglect) had impaired kinesthesia 100% of the time, whereas only 59% of participants without neglect were impaired. For those without neglect, we observed that a higher percentage of participants with lower but passing BIT scores displayed impaired kinesthetic behavior (78%) compared with those participants who scored perfect or nearly perfect on the BIT (49%). Conclusions. The presence of visuospatial neglect after stroke is highly predictive of the presence of kinesthetic deficits. However, the presence of kinesthetic deficits does not necessarily always indicate the presence of visuospatial neglect. Our findings highlight the importance of assessment and treatment of kinesthetic deficits after stroke, especially in patients with visuospatial neglect.